Analisis Majas Hiperbola yang Terkandung dalam Puisi yang Bertema Tentang “Cinta” Karya Sapardi Djoko Damono - Yosefa De Ancieta; Katharina Woli Namang; Yeremias Bardi; Trisnawati Bura (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This research aims to analyze the figure of speech of Figurecara (hyperbola) contained in a poem of Karya Sapardi Djoko Damono. This research method used a descriptive method. Judging from the secondary data source of this problem formulation is sourced from internet sites besides that, also the supporting source or complete in the discussion of this issue from the literature study research. The data used in this study was that the short story by Eka Kurniawan, a data analysis text used the reading methods. The results showed that we found many of Figure of speech (Figure of hyperbola) in every stanzas we might find when reading the poem.